Securitization and Nationalism in the Narrative of Rohingya Refugees in Bangladesh - Khairunnisa Girinoto, Athiyyah Puja (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2026)
This paper analyzes how the security narrative regarding Rohingya refugees is shaped by the Bangladeshi government through the process of securitization. Initially, the government's response to the influx of Rohingya refugees, following the 2017 ethnic cleansing in Myanmar, was dominated by a humanitarian narrative. However, as the refugee numbers exceeded 1.2 million, this phenomena led to increasing domestic pressures related to socio-economic burdens, resource competition, and social tension, the narrative shifted towards national security concerns. This paper use the Copenhagen School’s securitization theory and a qualitative case study method with discourse analysis in order to find how the Bangladeshi government, as the securitizing actor, uses specific speech acts such as framing refugees as a 'burden' and 'regional threat' to elevate the issue from a humanitarian crisis to a national security threat. This process is amplified by exclusive nationalism in the media, creating an 'us vs them' dichotomy that isolates refugees. The successful securitization has legitimized restrictive policies, including mobility restrictions and relocation to Bhasan Char Island. This demonstrates that securitization serves as a political tool to reshape policy and public perception in the name of national security